2009
DOI: 10.1123/japa.17.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin-D-Receptor Genotypes and Bone-Mineral Density in Postmenopausal Women: Interaction with Physical Activity

Abstract: The current study investigated the association between vitamin-D-receptor (VDR) genotypes with bone-mineral density (BMD) and its interaction with physical activity level (PAL). Individuals in a sample of 192 volunteers (67.84 ± 5.23 years) underwent BMD evaluation and were genotyped for VDR ApaI, BsmI, FokI, and TaqI polymorphisms. Haplotypes were reconstructed through expectation-maximization algorithm, and regression-based haplotype-specific association tests were performed with studied phenotypes. None of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
0
18
2
Order By: Relevance
“…The detailed optimized multiplex single-base extension protocol, with reactant concentration and PCR thermocycling conditions, has been reported elsewhere. 21 , 3133 …”
Section: Methodsmentioning
confidence: 99%
“…The detailed optimized multiplex single-base extension protocol, with reactant concentration and PCR thermocycling conditions, has been reported elsewhere. 21 , 3133 …”
Section: Methodsmentioning
confidence: 99%
“…If these genes had SNPs in their cis -regulatory elements, such as the promoter and enhancer, gene expression could be altered, and the SNPs and other structure variants could eventually cause the phenotype. The Block10 region that contains Tbsq4 is syntenic to human Chr12q12-13.3, where several bone-related SNPs have been assigned from GWAS (Bezerra et al 2008; Gentil et al 2007, 2009; Kim et al 2007; Pérez et al 2008; Dundar et al 2009; Mencej-Bedrač et al 2009; Pluskiewicz et al 2009; Timpson et al 2009; Zmuda et al 2009). Identification of the causative gene(s) for Tbsq4 should facilitate our understanding of the genetic regulation of bone structure in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that study showed that bone benefited from physical activity regardless of genotype. Moreover, Blanchet et al 28 and Gentil et al 7 showed that the dominant genotype is associated with increased BMD in physically active women. Tsuritani et al 11 found that the recessive genotype is more responsive to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interaction between VDR gene polymorphism and physical and functional performance, studies have shown that the dominant effect is associated with increased BMD in physically active women 7,13 . Moreover, Tsuritani et al 11 found that the recessive allele is more responsive to physical exercise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation